Developing and testing the congruency of selected biological indicators and an existing tool designed to assess wetland health in agricultural settings in the KZN Midlands - Kubheka, Patrick Skhumbuzo (Rhodes University, Faculty of Science, Department of Environmental Science, 2018)
Despite the fact that wetlands have been understood to be important for a wide range of ecosystem services, wetlands continue to be degraded globally. There has been a growing need to develop biomonitoring tools that reflect the present ecological state of wetlands, but very few attempts have been made in South Africa to achieve this, and those that have attempted this have generally achieved limited success. This study was conducted to develop and test the congruency of four selected biological indicators (dragonflies, frogs, macroinveterbrates and plants) in relation to the assessment of present ecological state using an existing method in South Africa, "WET-Health". WET-Health assessments rely primarily on transformations to a wetland that result from human impacts in both the catchment and the wetland itself. Using the tool, a health score is obtained that is consistent with the Department of Water Affairs (DWA) current "present ecological state" as applied to river health assessment. The study was conducted in agricultural settings of the Midlands of KwaZulu-Natal based on 13 wetlands. The selected wetlands were scored using WET - Health and grouped in four different ecological condition classes (A, B, C and D). Physical characteristics (wetland area, mean depth), biological characteristics (species cover/abundance, presence and species richness), and chemical characteristics (ammonia, pH, sulphate, nitrogen and phosphate) were also recorded in the selected wetlands. Nineteen different species of dragonfly were recorded in this study. The study demonstrated that dragonflies are a promising bioindicator of wetland present ecological state as the dragonfly index was found to be closely correlated with WET- Health scores. Open water bodies within the selected wetlands were the focus of dragonfly sampling, as male dragonflies are territorial and they will patrol or be found around this habitat. Emergent vegetation dominated by sedges formed the focus of macroinvertebrate sampling in this study because greater numbers of macroinvertebrate families were found in this biotope in comparison to open water areas with no emergent vegetation. A total of 47 macroinvertebrate families were recorded in this study, but SASS5 scores based on macroinvetebrates showed no correlation with WET-Health scores. A total of 10 different frog species were recorded in this study. All the species were common frog species found in most parts of the country. Frog species richness and occurrence showed no correlation with WET- Health scores. A total of twenty samples of two meter radius were measured per wetland and sampled for plant species and estimation of cover-abundance of each species per sample. Over 50 different plant species were recorded in this study, and both species accumulation and species richness showed a degree of correlation with WET-Health scores. All the wetlands in class A had generally higher species accumulation rate and species richness compared to the other wetland classes. In addition to testing the congruency of four selected biological indicators with WET- Health, water quality was measured in all the wetlands. Wetlands in class A were associated with improved water quality as the water passes through the wetland. However, wetlands in class C and D did not show consistently improved water quality between the apex and the toe of these wetlands. In some cases the water quality deteriorated as it passed through wetlands in these two classes.
Keywords: Wetland conservation -- South Africa -- KwaZulu-Natal; Wetland management -- South Africa -- KwaZulu-Natal; Wetland ecology -- South Africa -- KwaZulu-Natal; Ecosystem services -- South Africa -- KwaZulu-Natal; Environmental monitoring -- South Africa -- KwaZulu-Natal; Water quality biological assessment -- South Africa -- KwaZulu-Natal